Mekanisme Self Assessment System Dalam Pemungutan Pajak Penghasilan - Gaspersz, Alex; Nirahua, Salmon Eleazer Marthin; Tita, Heillen Martha Yosephine (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2025)
This article analyzes the implementation of the self-assessment system mechanism in the implementation of Income Tax (PPh) Article 21 collection, which is collected by a third party. The aim of this research is to confirm the self-assessment system as a mechanism for collecting income tax mandated by the 1983 tax reform and implied in Article 12 paragraph (1) KUP Law. The method used in this research is normative legal with a statutory approach and a conceptual approach. The results found that the collection of Income Tax Article 21 was carried out using a withholding system mechanism which was an introduction and an integral part of the self-assessment system mechanism.